Estudio de la respuesta tisular a una asociación experimental uncaria tomentosa willd D.C.- hidróxido de calcio versus cemento convencional de Groosman - Gutiérrez Lara, Juan Pablo (2003)
The present study evaluated biocompatible properties of a mixed cement with association of Uncaria tomentosa (Willd) D. C. and Calcium Hidroxide, compared to Grossman –like cement (Endofill), 37 rats sex male, three age months white race American Holdzman. With 300gr. of weight were used. An animal was sacrificed without placing him any implants lo evaluate normal anatomy of rats. The other groups were divided in: group A or control, with empty, implants hole; group B with mixed cement association; and the groups C, with Grossman-like cement. It was positioned 2 implant in each animal with the material to evaluate, one to each side of the loin. The animals were sacrificed after periods of 1,2,3 7 and 21 days. After obtaining the samples, microscopic analysis demonstrated that in the first two periods, all cements produced a acute type inflammation, all materials produced inflammatory reaction, however control groups and Group B corresponding to mixed cement association, showed the smallest inflammation level. Also, in Group B were observed notorious fibroblastic tissular reaction, the Grossman like cement with zinc oxide-eugenol, demonstrated bigger tissular inflammatory reaction, which diminished in the last period inflammatory reaction in the mixed cement association was of minor intensity showing an acceptable histologic reaction. It could be considered as an acceptable biologic material.